Addressing immunization gaps in children with congenital heart disease - a narrative review - Jecan - Toader, Diana; Filip, Cristina; Cainap, Simona Sorana (Medicine and Pharmacy Reports, 2025)
Vaccination programs have had a pivotal part in the successful reduction of global morbidity and mortality of infectious diseases. Despite their undeniable success, vaccination rates among children with congenital heart disease (CHD) remain suboptimal. This article aims to address the challenges surrounding immunization in CHD patients and provide guidance for immunization practices within this population. Most experts advocate for adherence to standard immunization practices in CHD patients who are immunocompetent and in good health. Supplemental vaccinations against rotavirus, varicella, meningococcus, hepatitis A and influenza are recommended. RSV prophylaxis with palivizumab is advisable in patients with hemodynamically significant CHD during winter season. However, special considerations are warranted in specific situations, such as around cardiac surgery or in patients who are immunocompromised. Furthermore, adjustments to the vaccination schedule might be necessary for patients who require antithrombotic prophylaxis or blood transfusions. Lastly, special attention should be given to individuals at a high risk of decompensation after immunization, who might require close parental or medical monitoring for up to 72 hours post-vaccination.